Usefulness of temporal bone prototype for drilling training: A prospective study. (2nd March 2017) - Aussedat, C.; Venail, F.; Nguyen, Y.; Lescanne, E.; Marx, M.; Bakhos, D.
Abstract : Objectives: Dissection of cadaveric temporal bones (TBs) is considered the gold standard for surgical training in otology. For many reasons, access to the anatomical laboratory and cadaveric TBs is difficult for some facilities. The aim of this prospective and comparative study was to evaluate the usefulness of a physical TB prototype for drilling training in residency. Design: Prospective study. Setting: Tertiary referral centre. Participants: Thirty‐four residents were included. Seventeen residents (mean age 26.7±1.6) drilled on only cadaveric TBs (" traditional " group), in the traditional training method, while seventeen residents (mean age 26.5±1.7) drilled first on a prototype and then on a cadaveric TB (" prototype " group). Main outcome measures: Drilling performance was assessed using a validated scale. Residents completed a mastoid image before and after each drilling to enable evaluation of mental representations of the mastoidectomy. Results: No differences were observed between the groups with respect to age, drilling experience and level of residency. Regarding drilling performance, we found a significant difference across the groups, with a better score in the prototype group ( P =.0007). For mental representation, the score was statistically improved ( P =.0003) after drilling in both groups, suggesting that TB drilling improves the mental representation of the mastoidectomy whether prototype or cadaveric TB is used. Conclusion: The TB prototype improves the drilling performance and mental representation of the mastoidectomy in the young resident population. A drilling simulation with virtual or physical systems seems to be a beneficial tool to improve TB drilling.